2015
DOI: 10.3136/fstr.21.733
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Rutin-rich Bread Made with ‘Manten-Kirari’, a Trace-rutinosidase Variety of Tartary Buckwheat (<i>Fagopyrum tataricum</i> Gaertn.)

Abstract: The rutin content of dough made with 'Manten-Kirari', a new Tartary buckwheat variety with tracerutinosidase activity and minimal bitterness, was assessed in a time course study of rutin hydrolysis in doughs with various water contents and blending ratios of Tartary buckwheat flour. In the normal rutinosidase variety, 'Hokkai T8', the majority of rutin was hydrolyzed within 30 min of water addition, whereas about 90% of rutin remained in 'Manten-Kirari'. We also investigated the residual rutin ratio in white b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 24 publications
0
23
0
1
Order By: Relevance
“…By scalding TB flour with hot water, a considerable amount of rutin is conserved from flour through the process to the final bread product (Lukšič et al 2016). Suzuki et al (2002Suzuki et al ( , 2014Suzuki et al ( , 2015aSuzuki et al ( , 2015bSuzuki et al ( , 2015c used new trace-rutinosidase TB variety to produce wheat-TB combined bread with considerable amount of rutin, preserving about 50% of the initial rutin from TB flour in the bread. Trace-rutinosidase TB may become more popular in Japan.…”
Section: Rutin Rutinosidase and Quercetinmentioning
confidence: 99%
“…By scalding TB flour with hot water, a considerable amount of rutin is conserved from flour through the process to the final bread product (Lukšič et al 2016). Suzuki et al (2002Suzuki et al ( , 2014Suzuki et al ( , 2015aSuzuki et al ( , 2015bSuzuki et al ( , 2015c used new trace-rutinosidase TB variety to produce wheat-TB combined bread with considerable amount of rutin, preserving about 50% of the initial rutin from TB flour in the bread. Trace-rutinosidase TB may become more popular in Japan.…”
Section: Rutin Rutinosidase and Quercetinmentioning
confidence: 99%
“…Hydrothermal processing at 100°C for 30 min and 121°C for 20 min or 30 min resulted in significantly decreased specific volumes of TB enriched CSB, with processing at 100°C for 30 min and 121°C for 10, 20 or 30 min leading to markedly increased hardness of CSB. Smaller specific volumes (Suzuki et al, 2015;Piasecka-j o zwiak et al, 2016) and increased hardness (Piasecka-j o zwiak et al, 2016) were also found in buckwheat enriched breads. Compared with control, the bitterness of CSB was sensitive to hydrothermal processing and decreased dramatically with processing time and temperature.…”
Section: Conditionmentioning
confidence: 96%
“…Za nobeno drugo metodo priprave kruha iz moke tatarske ajde ni znano, da bi se med postopkom priprave kruha ohranilo toliko rutina. Suzuki et al (2015) so nedavno poročali o tem, da so ob uporabi tatarske ajde s samo sledovi rutinozidaze pripravili kruh iz mešanice moke te tatarske ajde in pšenice z 0,63 mg/g rutina, kar predstavlja približno 50 % delež ohranjenega rutina v kruhu, v primerjavi z izvorno surovino (moko). Wieslander et al (2011) so poročali o koncentraciji 2,5 mg/g rutina prisotnega v piškotih, pripravljenih iz moke tatarske ajde.…”
Section: Hidrotermična Obdelava Tatarske Ajde Je Ovirala Pretvorbo Ruunclassified